Exploring Hemingway's Depiction of War Violence: Psychological and Societal Impacts in Selected Novels - Emad Mohammad Abbar (Academia Open, 2024)
This study delves into the portrayal of war violence in four seminal novels by Ernest Hemingway, namely, "A Farewell to Arms," "For Whom the Bell Tolls," "The Sun Also Rises," and "To Have and Have Not." Employing a qualitative analysis, this research categorizes instances of war violence based on thematic implications, narrative techniques, and character responses, while considering contextual information from Hemingway's own wartime experiences. The analysis unveils that Hemingway's exploration of war violence transcends the physical battlefield, emphasizing the profound psychological traumas, moral quandaries, and societal scars it inflicts. Characters within these narratives grapple with disillusionment, existential anguish, and a sense of alienation, reflecting the multifaceted impacts of war on individuals and society. Hemingway's personal involvement in World War I and the Spanish Civil War greatly influences his portrayal of war violence, presenting it as not only an external conflict but an internal struggle that challenges ideologies, identities, and human resilience. The thematic recurrence across these novels underscores Hemingway's persistent examination of the enduring consequences of war. In essence, Hemingway's depiction of war violence serves as a lens through which to contemplate the profound psychological and societal repercussions of conflict, offering an enduring reflection on the devastating nature of war. Highlights : Qualitative analysis of Hemingway's war narratives. Psychological and moral dilemmas in war literature. Hemingway's personal experiences and their literary influence. Keywords : War Violence, Hemingway Novels, Psychological Impacts, Societal Consequences, Qualitative Analysis